Fostering inclusivity: Transforming South African school music programmes through the dalcroze approach - Yende, Sakhiseni Joseph (Edelweiss Applied Science and Technology, 2024)
This article explores the transformative potential of the Dalcroze Approach in South African school music programs, with a focus on fostering cultural inclusivity. Employing a qualitative research methodology grounded in content analysis, the study systematically examines diverse sources, including archival materials, books, and peer-reviewed journal articles. The triangulation method enhances the robustness of data by cross-referencing information from platforms like Google Scholar, JSTOR, ResearchGate, and university repositories. The Dalcroze Approach, rooted in holistic and embodied learning experiences, emerges as a transformative pedagogy with the capacity to address historical disparities and celebrate South Africa's diverse musical traditions. Findings indicate a compelling alignment between the approach and inclusivity goals, emphasising the adaptability of the Dalcroze principles to the nation's cultural tapestry. The findings of this article reveal that educators, administrators, and students play pivotal roles in shaping the success of implementing the Dalcroze Approach. Educators witness positive impacts on student engagement and creativity, administrators recognise its strategic value, and students experience a transformative shift in their music learning journey. In conclusion, this article advocates for comprehensive professional development programs, collaboration with curriculum developers, and ongoing research initiatives to ensure the sustained integration of the Dalcroze Approach. By embracing this transformative pedagogy, South African music education can evolve into a more inclusive and culturally responsive domain, reflecting the nation's rich musical heritage.